Modelling and analyses of the mechanical response of P92 steel in stress-controlled cyclic tensile-loading tests with holding periods. (1st November 2020) - Huang, Qingyang; Cai, Xiaodan; Ji, Dongmei; Wang, Jiong
ABSTRACT: The current study investigates the mechanical behaviors of P92 steel in the stress-controlled cyclic tensile-loading tests with holding period. First, the testing conditions and some typical experimental results of P92 steel in those kind of tests are reviewed. To simulate the mechanical behaviors of P92 steel, a three-stage creep model is adopted. The material parameters in the model are identified by using the experimental data of pure creep tests, where the low- and high-stress ranges are considered separately. The constitutive equations of the model can be solved through a conventional numerical approach. With the obtained numerical results, the responses of P92 steel samples in the cyclic tensile-loading tests with holding periods can be predicted at a quantitative level. Some key features of the experimental results are also analyzed. Furthermore, the damage evolution property of P92 steel in the tests can be revealed. The current modelling work will be helpful for the residual lifetime evaluation and the safety design of P92 steel components under practical loading conditions.